Study on Crystal Structure, Surface Area, and Energy Gap Behaviors of Nanotitania Polymorphs Prepared Using Monoethanolamine - Manurung, Posman; Maharani, Renita; Rahmayanti, Dita; Yulianti, Yanti; Junaidi; Marjunus, Ronius (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2024)
Polymorphous nanotitania samples were prepared from titanium butoxide (TTB) as a precursor using sol-gel processing in ethanol as a solvent, without and with monoethanolamine (MEA). The experiments used 5.25 mL TTB and MEA with varied volumes of 0.5, 1.0, 1.5, and 2.0 mL. The sample without MEA was specified as sample A, and the samples produced using MEA were specified as samples B, C, D, and E, respectively. All samples were calcined at 500 °C for 4 h and then collected data by X-ray Diffraction (XRD), the Brunauer-Emmett-Teller (BET) method used to analyze Surface Area Analyzer (SAA), Transmission Electron Microscopy (TEM), Raman Spectroscopy, and UV-Visible Diffuse Reflectance Spectroscopy (UV-Vis DRS). The results of XRD characterization indicate that samples A and B form anatase phase, while samples C and D are composed of anatase, brookite, and rutile phases, and sample E is consisted of anatase and brookite phases with weight percentages of (94.53 ± 1.72) % and (5.47 ± 0.36) %, respectively. The presence of the three phases of titania is also confirmed by Raman spectroscopy analysis, which showed anatase peaks at 146, 197, 398, and 513 cm-1, brookite peaks at 245 and 402 cm-1, and rutile peaks at 319, 436, and 612 cm-1. According to XRD, the samples have the particle size in the range of 14-19 nm. A representative sample (sample C) was also characterized using TEM, revealing a particle size of 16.0 ± 0.3 nm. This representative sample revealed the largest surface area of 172.2 m2/g, as seen by BET, and the lowest energy gap of 3.03 eV.